2012
DOI: 10.1007/s00296-012-2622-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adult patients with Familial Mediterranean fever living in Germany or Turkey compared to healthy subjects: a study evaluating the effect of disease severity and country of residence

Abstract: We assessed quality of life (QOL) and disease activity in patients with Familial Mediterranean fever (FMF) of Turkish ancestry living in Germany or Turkey and conducted a correlation with FMF disease activity. 40 FMF patients in Turkey (TR), 40 FMF patients in Germany (G) and 40 healthy controls in Germany (C) were included. QOL was evaluated with the short form of the World Health Organisation Quality of Life scale (WHOQOL-BREF). FMF disease activity was examined with the Pras score. Mean age was TR 30.5 ± 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
1
23
2
2
Order By: Relevance
“…In that study patients with anxiety and depression also had a decrease in the mental component scores when compared to controls. Also Giese et al who examined 40 Turkish and 40 German patients with FMF and 40 controls by the World Health Organization Quality of Life scale (WHOQOL-BREF) found decreased HRQoL only in physical concepts [16]. This was in contrast to 2 studies of 51 children and adolescents and 100 adults with FMF that demonstrated decreased physical and emotional HRQoL measured by the Pediatric QoL Inventory Generic Core Questionnaire and SF-36, respectively [13, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study patients with anxiety and depression also had a decrease in the mental component scores when compared to controls. Also Giese et al who examined 40 Turkish and 40 German patients with FMF and 40 controls by the World Health Organization Quality of Life scale (WHOQOL-BREF) found decreased HRQoL only in physical concepts [16]. This was in contrast to 2 studies of 51 children and adolescents and 100 adults with FMF that demonstrated decreased physical and emotional HRQoL measured by the Pediatric QoL Inventory Generic Core Questionnaire and SF-36, respectively [13, 15].…”
Section: Discussionmentioning
confidence: 99%
“…There is a debate whether there is a correlation between the frequency of attacks and HRQoL with Buskila et al and Makay et al finding a significant correlation with the attack frequency [11, 13], while Sahin et al and Giese et al did not [15, 16]. Since all patients in our study had very frequent attacks (nearly one per week in the screening month), it was not surprising that we did not find this to be a significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the high prevalence of appendectomy among patients with FMF of Turkish ancestry living in Germany could be related to later diagnosis and treatment of FMF and appendectomies performed to treat febrile attacks before FMF is diagnosed. Familial Mediterranean fever is a rare condition in Germany, and a longer delay between first symptoms of FMF and initiation of colchicine treatment in Germany compared to Turkey (14.2 ± 10.2 versus 6.8 ± 8.7 years; P < .001) has been described 19 . Possible language barriers for Turkish migrants accessing the German health care system 10 might also contribute to FMF‐associated generalized peritonitis and acute febrile attacks 1 , 2 being mistaken for appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the course of FMF in regions where it is endemic and where it has low prevalence have shown conflicting results as to whether regional variations are associated with differences in disease severity. [16][17][18][19][20][21] Splenomegaly is not a finding specific to FMF but may be associated with a wide variety of diseases, including viral or bacterial infections, hematologic diseases, portal hypertension, storage diseases, amyloidosis, and acromegaly. The normal spleen weight is known to range between 150 and 180 g. 22 The normal dimensions of the spleen (thickness × width × length) are commonly assumed to be 7 × 4 × 11 cm, although a spleen width of 5 cm or less is also considered physiologic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation